BODILY CULTURE AND BODILY EDUCATION OF HUMAN (EDUCATION IN THE 21ST CENTURY, 2023)
Today, the corporeal has taken a solid place in public space. The active position of a personin relation to his body and physical perfection is concretized in different types of behavior, thebody actively participates in various kinds of demonstrations, games, and competitions. Forexample, some people are consciously engaged in fitness, aerobics, bodybuilding, dancing, yoga,shaping, making tattoo, piercing, doing plastic surgery, visiting solarium, saunas, and massagecenters for the optimal body care. The values of body formation should include health preservationand strengthening, muscle development, optimal preparation for the needs of military service, therecovery of the lost body functions, the formation of movement culture, physique. Suchapproaches must go hand in hand with the development of intelligence, memory, thinking,creativity, aesthetic and moral qualities.Physical education and sports training refer to those areas in which, like nowhere else, humancorporeality is manifested in its cultural aspect.80The primary purpose of this research is to highlight the essence and content of thephenomenon of bodily culture and bodily education of human through the prism of physicaleducation and sports training process. The article discusses and summarizes the values for theformation of human corporeality, issues of bodily culture and bodily education relying onpedagogical, philosophical, sociological literature sources. Some methods and techniques,programs and concepts of bodily culture and bodily education are highlighted.
Keywords: Body, Physique, Movement culture, Bodily education.